The study on the relationship between the principle instagram account and the dropship sales: the case of hijab instagram sellers in Sarawak. - Norazakiah Niffer Yaman. (2017)
This study was conducted to see the relationship between the principle and instagram account and the dropship sales: The case of sarawak instagram hijab sellers. The method used to collect data is through interviews with dropship sellers.